Desain Aplikasi Antrian Berbasis Android - Yosafat Setia Budi; Henry Novianus Palit; Yulia Yulia (Jurnal Infra, 2016)
Waiting is a boring thing for most people. Moreover, if a person waiting in a very long queue. It provides a deterrent effect because they do not know how much longer they must to wait to get a service.Therefore, they invented a queueing system Android-based application that can provide information on the estimated waiting time for the Customer who is in a queue, so that they can know time estimation when they will be served. Android app on this thesis has a feature displays the current queue information required by the Customer and the current estimation waiting time, the queue number being served now, as well as the number of people waiting before the Customer. Customer ticket information delivered to the Android application with a feature of Google Cloud Messaging (push notification). From the test results, the system can generate the estimated waiting time of about 65.51% without tolerance over time and reached 67.95% with a tolerance of +/- 2 minutes. The results obtained using historical data held by an agency or organization.